Crucial Role for Endothelial Cell α2β1 Integrin Receptor Clustering in Collagen‐Induced Angiogenesis. Issue 6 (31st October 2019) - Turner, Kevin R.; Adams, Christopher; Staelens, Stephanie; Deckmyn, Hans; San Antonio, James
ABSTRACT: Angiogenesis is a crucial mechanism of vascular growth and regeneration that requires biosynthesis and cross‐linking of collagens in vivo and is induced by collagen in vitro . Here, we use an in vitro model in which apical Type I collagen gels rapidly induce angiogenesis in endothelial monolayers. We extend previous studies demonstrating the importance of the endothelial α2β1 integrin, a key collagen receptor, in angiogenesis by investigating the roles of receptor clustering and conformational activation. Immunocytochemical localization of α2β1 integrins in endothelial monolayers showed a concentration of integrins along cell–cell borders. After inducing angiogenesis with collagen, the receptors redistributed to apical cell surfaces, aligning with collagen fibers, which were also redistributed during angiogenesis. Levels of conformationally activated α2β1 integrins were unchanged during angiogenesis and undetected on endothelial cells binding collagen in suspension. We mimicked the polyvalency of collagen fibrils using antibody‐coated polystyrene beads to cluster endothelial cell surface α2β1 integrins, which induced rapid angiogenesis in the absence of collagen gels. Clustering of αvβ3 integrins and PECAM‐1 but not of α1 integrins also induced angiogenesis. Soluble antibodies alone had no effect. Thus, the angiogenic property of collagen may reside in its ability to ligate and cluster cell surface receptors such as α2β1 integrins. Furthermore, synthetic substrates that promote the clustering of select endothelial cell surface receptors mimic the angiogenic properties of Type I collagen and may have applications in promoting vascularization of engineered tissues. Anat Rec, 2019. © 2019 American Association for Anatomy